Occlusal Morphology of Primary Molars in Anganwadi Children, Faridabad - Brinda Khanna1 , Archika Singh1 , Nisha Rani Yadav2, Meena Jain3 , Ankur Sharma4 , Vishal Jain5 , Ak (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction - Forensic odontology helps in identifying any suspect involved in crime, in accidental cases, in disaster victim identifications. Teeth shows variation in its anatomy as it has a very strong hereditary component. Variations in occlusal morphology of teeth include differences in the number of cusps and the fissure pattern. So, it is important to know the occlusal morphology of teeth in Forensic odontology. Materials and Method - A descriptive study was conducted to evaluate the cusp and groove pattern in primary second molar of 3-6 year old children from Anganwadis of Faridabad. Hellman and Gregory’s criteria for groove pattern were used to know the buccal groove pattern and cusps of primary molar. Data were analyzed with SPSS statistics software 23.0 version. Result - The predominant groove pattern was “Y” (73.34%). Majority of the participants has 5 cusps in primary second molar. 67.45% of the study participants had 5Y occlusal morphology of primary mandibular second molar and it is mostly seen in male children. Conclusion - This occlusal configuration will further help in various genetic, anthropological and forensic investigations. Furthermore, knowing common variations in dental anatomy and morphology about each individual tooth can help in providing dental treatments such as restorative, endodontic and orthodontic treatments